Screening for Maladjustment in College Students: An Application of Receiver Operating Characteristic Curve to MMPI Scales - Svanum, Soren; Ehrmann, Lisa C. (Journal of personality assessment, 1993)
The ability of two scales derived from the Minnesota Multiphasic Personality Inventory (MMPI) to identify emotional maladjustment in a college setting was examined. The scales were the College Maladjustment scale (Mr) developed by Kleinmuntz (1961) and the Health Opinion Survey based Emotional Disorder scale (Ed). Emotional maladjustment was defined by criteria established in the Diagnostic and Statistical Manual of Mental Disorders (3rd ed., rev. [DSM-III-R]; American Psychiatric Association, 1987) and assessed through a computerized Diagnostic Interview Schedule. Subjects were 94 female and 62 male students, 51 of whom (33%) met criteria for at least one DSM-III-R disorder. Substance use disorders were most frequent (13.5%), followed by anxiety disorders (11.5%) and depressive disorders (7.1%). Both Mt and Ed had no relationship to substance use disorders but were moderately related to nonsubstance use maladjustment (r = ≈47); receiver operating characteristic (ROC) analysis was employed, and Mt and Ed proved to be a fair-to-good indicator of nonsubstance use maladjustment. Types of decision errors are discussed, and tables provide information concerning predictive accuracy across the entire range of scores.